Agroecology and integral microfinance: recommendations for the Colombian post-conflict avoiding the financialization of rural financing (2019)
One of the main challenges for the Colombian post-conflict is to develop sustain-able proposals for peasant families that were affected by the armed conflict. With the purpose of analyzing this challenge, after the introduction, the second part of the paper presents the land possession dyna-mics in Colombia, criticizes the Green Revolution approach and discusses theoretical concerns about agroecology. The third section highlights the importance of combined microfinance in comparison to financialized microfinance, for financing rural projects and agroecology. Further-more, this part argues that the combination of agroecology and combined microfi-nance is a powerful tool to make scenarios sustainable for small producers. Finally, the fourth section concludes.